Development of Electron Transfer Mediator Using Modified Graphite Oxide/Cobalt for Enzymatic Fuel Cell. Issue 10 (1st January 2015) - Kim, Dong Sup; Kim, Sung Bong; Yang, Xiaoguang; Lee, Ja Hyun; Yoo, Hah Young; Chun, Youngsang; Cho, Jaehoon; Park, Chulhwan; Lee, Jinyoung; Kim, Seung Wook
Abstract : In an enzymatic fuel cell system, mediation of electron transfer is one of most important components supporting enzymes on electrode surfaces and transferring electrons from oxidation reaction. Various materials were tested as mediators for efficient electron transfer. The electrode preparation process was optimized using the selected material. Cobalt (Co) showed good performance as an electron transfer mediator. CoCl2 of 0.02 mol was the most effective concentration for a high-quality graphite oxide (GO)/Co composite. A reaction time of 18 h was optimal for significantly improved power density. Self-assembled glucose oxidase (GOx) and laccase were used as the anode biocatalyst and cathode biocatalyst, respectively, on Au electrodes. The enzymatic fuel cell produced a cell voltage of −0.578 V vs Ag/AgCl. The highest power density (1, 058 μW/cm 2 ) was generated at the optimal condition. Molecular properties of the developed electron transfer mediator using Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) were identified by observing the changes of the composite at the micro-surface level.